Decomposition of Wealth and Income using Micro Data from Austria - Peter Lindner (Oesterreichische Nationalbank (OeNB), 2011)
This paper analyses Austrian data on (financial) wealth and income. The main focus lays on the distribution of these indicators. Using a decomposition procedure of the Gini Index first proposed by Lerman and Yitzhaki (1985), it is possible to recover the effect of specific forms of investments of assets and of certain sources of income on the overall distribution (in terms of an elasticity) of wealth and income in Austria. For the first time Austrian wealth and income data are used to decompose the total distribution into various categories. Additionally, there are, due to the lack of available data on household wealth, internationally only very few attempts to compare wealth and income using decomposition methods. The analysis shows that specific forms of assets (mainly more sophisticated ones) as well as income from sources that are concentrated on a small group tend to increase inequality whereas the others have an equalizing effect.
Keywords: D3; 330; Wealth distribution; income distribution; decomposition by components/